El concepto de forma "un principio que fundamenta el acto creativo en el taller de diseño” (2020)
Within the wide interpretation of the visual language and its different uses in the contemporary creation, this paper seeks to develop an interpretation of such creation taking into account an understanding of representation as a permanent design expression. With this purpose in mind, the article seeks to understand Form as a key concept of analysis in design. To do so, the article takes into account the conceptual framework that is used in the creation of artifacts, in which such creation is transformed due to the visual elements that are put together. The paper assesses various principles about Form from several authors' standpoints in order to offer an explanation of Form and its contents.